The impact of tropical storm Ondoy on Marikina Polytechnic College Library with implications on the development of a disaster plan - Balquiedra, John Patrick M. (2014)
Disasters can occur in different forms. A disaster in the library is an unforeseen event which puts collection at risk. Natural disasters cannot be prevented, but measures can be taken to eliminate or reduce the possibility of damages. The Philippines is very prone to different kinds of hazards. Each year, about 20 typhoons occur in the Philippine area of responsibility of which an average of 9.2 actually crosses the country. According to PAGASA (Philippine Atmospheric, Geophysical and Astronomical Services Administration), typhoons and storms bring the most damages to the country than any other natural phenomena.